2018
DOI: 10.1016/j.jsat.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Relapse to opioid use disorder after inpatient treatment: Protective effect of injection naltrexone

Abstract: Short term inpatient treatment is associated with a high rate of relapse among patients with opioid use disorder. These findings support the recommendation that medically supervised withdrawal from opioids should be followed by medication assisted treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…A secondary analysis (65) of the pivotal placebo-controlled study (27) showed that none of the 25 baseline factors predicted a positive clinical response to XR-NTX. Two secondary analyses (66, 67) of a large United States study comparing XR-NTX to treatment referral (28) found that XR-NTX induction setting interacted with opioid relapse and that of 36 baseline factors only alcohol use to intoxication moderated the treatment effect. Specifically, because relapse was higher among patients who received XR-NTX during a short-term inpatient stay, its protective effects were greater than those who received XR-NTX during long-term inpatient stays and in outpatient settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A secondary analysis (65) of the pivotal placebo-controlled study (27) showed that none of the 25 baseline factors predicted a positive clinical response to XR-NTX. Two secondary analyses (66, 67) of a large United States study comparing XR-NTX to treatment referral (28) found that XR-NTX induction setting interacted with opioid relapse and that of 36 baseline factors only alcohol use to intoxication moderated the treatment effect. Specifically, because relapse was higher among patients who received XR-NTX during a short-term inpatient stay, its protective effects were greater than those who received XR-NTX during long-term inpatient stays and in outpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“… a Details regarding induction setting reported in (67) b Details regarding induction setting reported in (75) c NTX-assisted detox XR-NTX induction rate significantly higher than buprenorphine-assisted detox d Numbers reported for patients who were recommended for XR-NTX …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The risk of early opioid treatment dropout is likely to be greater among participants actively using heroin and initially admitted to acute detoxification units than opioid patient cohorts initiating outpatient medication treatment. 28 Detoxification admissions typically represent a spectrum of motivation and treatment-seeking; many patients are in crisis and unclear of further treatment options, while other patients are highly motivated to begin a thoughtfully considered new treatment programme. The early randomisation group in this trial, who were more recently admitted and more recently using heroin (or other opioids) than the late randomisation group, had higher overall relapse events in both treatment groups than the late randomisation group.…”
Section: Discussionmentioning
confidence: 99%
“…prescription drug monitoring programs and prescriber guidelines) address primary prevention (reducing risk of incidence of OUD) or secondary prevention (early identification) but do not necessarily facilitate progression through the treatment end of the cascade for individuals once identified with OUD (far right of Figure 1). Further, expanding access to shortterm detoxification programs or "detox beds" cannot contribute to successful progression along the cascade unless these facilities are repurposed and entitled "medication initiation units" (40). Detoxification itself is not a treatment for OUD and when used in isolation increases risks of adverse events such as overdose (41).…”
Section: Treatment: Moud Initiation and Retention Beyond 6 Monthsmentioning
confidence: 99%